2006
DOI: 10.1002/anie.200600532
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Molecular Oxygen with a PdII– Hydride To Produce a PdII–Hydroperoxide: Acid Catalysis and Implications for Pd‐Catalyzed Aerobic Oxidation Reactions

Abstract: Palladium-catalyzed reactions are among the most versatile methods for the selective aerobic oxidation of organic molecules.[1] These reactions are generally thought to proceed by a two-stage "oxidase" pathway that consists of Pd II -mediated oxidation of the organic substrate followed by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 44 publications
5
80
1
Order By: Relevance
“…[65] Studies of O 2 insertion into Pd II ÀH bonds in non-pincerligated systems by Stahl et al revealed a different mechanism. [66][67][68][69] In this case, initial reductive elimination of HX from the Pd II hydride complex to generate a Pd 0 species (Scheme 8) is followed by reaction of the Pd 0 with O 2 to form an h 2 -peroxo complex (as described above). The Pd II -(h 2 -peroxo) is then protonated to generate the observed PdÀOOH moiety.…”
Section: Formal Insertion Of O 2 Into Pd II àH Bondsmentioning
confidence: 99%
“…[65] Studies of O 2 insertion into Pd II ÀH bonds in non-pincerligated systems by Stahl et al revealed a different mechanism. [66][67][68][69] In this case, initial reductive elimination of HX from the Pd II hydride complex to generate a Pd 0 species (Scheme 8) is followed by reaction of the Pd 0 with O 2 to form an h 2 -peroxo complex (as described above). The Pd II -(h 2 -peroxo) is then protonated to generate the observed PdÀOOH moiety.…”
Section: Formal Insertion Of O 2 Into Pd II àH Bondsmentioning
confidence: 99%
“…As shown in Table 1 (entries 1 and 2), in the presence of 2 mol % [Pd(OAc) 2 ] without any ligand only the well-known oxidation towards benzaldehyde occurred in fair yield. [13] Using methanol as solvent and adding K 2 CO 3 as base led to some cross-esterification product (43 % methyl benzoate). However, the reaction proceeded in a nonselective manner and the catalyst immediately turned black ( Table 1, entries [3][4].…”
mentioning
confidence: 99%
“…4−13 Insertion of O 2 into metal hydride bonds is often a key step in its activation, and metal hydroperoxide complexes are frequently the observed products of this reaction. Indeed, such reactions have been observed for hydride complexes of cobalt, 14 iridium, 15 palladium, 16,17 platinum, 18,19 and rhodium. 20−23 Accordingly, studies of the reaction of O 2 with metal hydride complexes are germane to expanding the scope and utility of aerobic oxidation reactions.…”
Section: ■ Introductionmentioning
confidence: 94%